A biofunctional review of C-reactive protein (CRP) as a mediator of inflammatory and immune responses: differentiating pentameric and modified CRP isoform effects - Olson, Margaret E.; Hornick, Mary G.; Stefanski, Ashley; Albanna, Haya R.; Gjoni, Alesia; Hall, Griffin D.; Hart, Peter C.; Rajab, Ibraheem M.; Potempa, Lawrence A. (Frontiers in Immunology, 2023)
C-reactive protein (CRP) is an acute phase, predominantly hepatically synthesized protein, secreted in response to cytokine signaling at sites of tissue injury or infection with the physiological function of acute pro-inflammatory response. Historically, CRP has been classified as a mediator of the innate immune system, acting as a pattern recognition receptor for phosphocholine-containing ligands. For decades, CRP was envisioned as a single, non-glycosylated, multi-subunit protein arranged non-covalently in cyclic symmetry around a central void. Over the past few years, however, CRP has been shown to exist in at least three distinct isoforms: 1.) a pentamer of five identical globular subunits (pCRP), 2.) a modified monomer (mCRP) resulting from a conformational change when subunits are dissociated from the pentamer, and 3.) a transitional isoform where the pentamer remains intact but is partially changed to express mCRP structural characteristics (referred to as pCRP* or mCRPm). The conversion of pCRP into mCRP can occur spontaneously and is observed under commonly used experimental conditions. In careful consideration of experimental design used in published reports of in vitro pro-and anti-inflammatory CRP bioactivities, we herein provide an interpretation of how distinctive CRP isoforms may have affected reported results. We argue that pro-inflammatory amplification mechanisms are consistent with the biofunction of mCRP, while weak anti-inflammatory mechanisms are consistent with pCRP. The interplay of each CRP isoform with specific immune cells (platelets, neutrophils, monocytes, endothelial cells, natural killer cells) and mechanisms of the innate immune system (complement), as well as differences in mCRP and pCRP ligand recognition and effector functions are discussed. This review will serve as a revised understanding of the structure-function relationship between CRP isoforms as related to inflammation and innate immunity mechanisms.